Awareness and willingness towards Micro Pension Schemes - a special reference to selected employees of artisan industries - N, Sunayana; Kumar, Ravi (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to understand the awareness and willingness towards Micropension schemes such as Atal pension yojana, an initiative by central government to secure the old age of unorganized sector employees. These are voluntary schemes and success of the same depends on the participation of employees in such schemes. The data was collected with the help of questionnaire circulated among 53 employees of 12 artisans industry situated in Mysore. The paper analyses the willingness on the basis of financial and psychological readiness. Irrespective of the age, the kind of information and source of information plays a major role in shaping willingness of an individual in determining the investments in Micro pension schemes. This study also proved that the respondents depend on suggestions of friends, relatives and coworkers. Generally, in the employees of unorganized sector, an individual experience with investment is considered more valuable than the printed matter or materials. Therefore, before administering an awareness programme, it is important to gain the trust of the target group. The amount of premium money, the kind of pension scheme, institution offering the scheme, amount of benefit supposed to be received during retirement, annuity also play an important role in creating financial readiness for investment in a pension scheme